Assessment of Synaptic Plasticity via Long-Term Potentiation in Young Mice on the Day after Acoustic Trauma: Implications for Tinnitus - Cakir, Asli; Ecevit, Mustafa Cenk; Bal, Ramazan; Gurkan, Selhan; Alpay, Hayrettin Cengiz; Serbetcioglu, Mustafa Bulent (Aves, 2015)
OBJECTIVE: This experimental study evaluated the pathophysiological association of long-term potentiation (LTP)-mediated synaptic plasticity in tinnitus in 30 BALB/c mice. MATERIALS and METHODS: Baseline hearing levels and tinnitus perception were examined with startle reflex time and gap detection time measurements using an acoustic stimulus of a 6 kHz pure tone at 90 db sound pressure level (SPL) on post-natal day 16. The acoustic trauma group was exposed to 6-kHz pure tone at 120 db SPL on post-natal day 16. On post natal day 17, the acoustic trauma group underwent re-measurements of hearing levels and tinnitus preception using an acoustic stimulus of 6-kHz pure tone at 100 db SPL. Fifteen tinnitus-induced and fifteen control subjects were sacrificed on post-natal day 17, and LTP in the dorsal cochlear nuclei of each animal was examined. RESULTS: With respect to gap detection time, there were no statistically significant between group differences; however, there was a statistically significant difference between the pre- and post-trauma period in the acoustic trauma group. Moreover, LTP was significantly higher in the acoustic trauma group than in the control group. CONCLUSION: The results suggest that LTP underlies tinnitus pathogenesis.
Keywords: Tinnitus; noise induced; neuronal plasticity; long-term potentiation; cohlear nucleus; acoustic trauma